Proxy wars suppressing violence through local agents - Berman, Eli 1960-; Lake, David A. 1956-; Macdonald, Julia (Cornell University Press, 2019)
"Analytical narratives examine when and where major powers can work through local proxies rather than commit their own troops. Cases include Denmark under Nazi occupation, the Korean War, El Salvador, Colombia, and present-day Iraq, Yemen, and Afghanistan. Most focus on the United States, but Israel's relations with Lebanon and Gaza and the Palestinian Authority are also featured"...
Includes bibliographical references and index
Keywords: Geschichte; Proxy war -- History -- 20th century -- Case studies; Proxy war -- History -- 21st century -- Case studies; Außenpolitik; Zweiter Weltkrieg; Kriegführung; Stellvertretung; Besetzung; United States -- Foreign relations -- 20th century -- Case studies; United States -- Foreign relations -- 21st century -- Case studies; Dänemark; USA; Aufsatzsammlung